WEBSITE DEVELOPMENT PROJECT FOR KAMPUNG SANTRI, INDONESIA - Azri Syafiq Bin Md Julis; Fadillah Binti Ismail; Muhammad Izzad Bin Luqman (Jurnal Penyelidikan Sains Sosial, 2020)
This study is a project base to develop a website as promoting and communication tool for residents of kampung Santri, Indosnesia. This study has applied a combination of quantitative and qualitative methods in obtaining data through the distribution of questionnaires, interviews and observations. Facing the challenge of industry revolution 4.0, Internet of Things, artificial intelligence and robotic become a new initiative to replace man power. A confused mind on these days will make future generation become uncompetitive regarding uses of technology. Therefore, this study is an effort by UTHM and UniBanten students through project under Real Work Lecture (KUKERTA) in ensuring community ability and mastering technology so that the residents of Kampung Santri can function effectively and not left behind in the twenty-first century.